3(-2+12)=8-2(n-8)

Simple and best practice solution for 3(-2+12)=8-2(n-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2+12)=8-2(n-8) equation:


Simplifying
3(-2 + 12) = 8 + -2(n + -8)

Combine like terms: -2 + 12 = 10
3(10) = 8 + -2(n + -8)

Multiply 3 * 10
30 = 8 + -2(n + -8)

Reorder the terms:
30 = 8 + -2(-8 + n)
30 = 8 + (-8 * -2 + n * -2)
30 = 8 + (16 + -2n)

Combine like terms: 8 + 16 = 24
30 = 24 + -2n

Solving
30 = 24 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
30 + 2n = 24 + -2n + 2n

Combine like terms: -2n + 2n = 0
30 + 2n = 24 + 0
30 + 2n = 24

Add '-30' to each side of the equation.
30 + -30 + 2n = 24 + -30

Combine like terms: 30 + -30 = 0
0 + 2n = 24 + -30
2n = 24 + -30

Combine like terms: 24 + -30 = -6
2n = -6

Divide each side by '2'.
n = -3

Simplifying
n = -3

See similar equations:

| x+0.05=36750 | | -2(6-10n)=10(2-6) | | 0.9x-2.2=3.5x+1.7 | | -5-8(1-x)=2(7x-6) | | x(9x-8)=(9x+8)(x-2) | | -102=-6(-7-6n) | | 5y=8-4(-2) | | 5/y+13/y=3 | | 3m-5=215 | | 4+3n=6n+4 | | 865=237+x | | 3a-5+19=-2 | | 5y-7y=5y+8y | | 3(3x-7)=2(8-3x) | | 2x+1/8=-3 | | X/8-1=6 | | 0=6x-2 | | 4+9x=292 | | 9(3x+2)=4 | | 2(x+26)=264 | | 1(3/11-7d/12) | | 7w-3(w-2)=20 | | 1=1+4p-4p | | 100(x-3)-8= | | 3n+15=18n | | x^2-x-6=x^2-6x+9 | | Y=x^4+12x^2+36 | | 4(2y-1)=-4 | | 3(-12)+47+(-12)+26=27+(-12)+10 | | -10=16 | | 14x-3x=22 | | 5x+26=3(x+1)-2x |

Equations solver categories